Length and density of filiform tongue papillae: differences between tick-susceptible and resistant cattle may affect tick loads - Cecília José Veríssimo; Selma Marques D’Agostino; Fernanda Ferreira Pessoa; Luciandra Macedo de Toledo; Isabel Kinney Ferreira de Miranda Santos (Parasites & Vectors, 2015)
Abstract Background Indicine breeds of bovines are highly resistant and taurine breeds are susceptible to the cattle tick, Rhipicephalus microplus, a species which causes great damage to livestock. Animals use their tongues for self-grooming, an important behavior for ridding themselves of ectoparasites. However, the role of tongue morphology, notably the filiform papillae, in this process is not known. Findings This study compared features of the filiform papillae of tongues in eight Nelores (indicine breed) and eight Holsteins and two Brown Swiss (taurine breeds) and verified how they associate with tick loads. Biopsies were taken from identical positions of tongues and measured by scanning electron microscopy. One-way analysis of variance detected significant differences between morphological features of tongues from indicine and taurine breeds: Nelores had longer papillae (mean of 2.3 mm ± 0.029 SD; P < 0.001), and more papillae per cm2 (mean of 25.2 papillae ± 1.92 SD; P < 0.05) than European bovines (means of, respectively, 1.8 mm ± 0.027 SD and 20.9 ± 0.74 SD papillae per cm2). After infestations with equal numbers of larvae, loads of adult ticks were inversely correlated with length of papillae and directly correlated with distances between the apices of papillae (P = 0.014; r = −0.566 and P = 0.018; r = 0.567, Pearson product momentum correlation, respectively). Conclusions Spacing between papillae is smaller in Nelores, thus their tongues may be rougher and, consequently, more effective in removing tick larvae during self-grooming, explaining the greater resistance to ticks among Zebu breeds of cattle.